2015
DOI: 10.1093/annonc/mdv112
|View full text |Cite
|
Sign up to set email alerts
|

Early tumor shrinkage and depth of response predict long-term outcome in metastatic colorectal cancer patients treated with first-line chemotherapy plus bevacizumab: results from phase III TRIBE trial by the Gruppo Oncologico del Nord Ovest

Abstract: FOLFOXIRI plus bev improves ETS and DoR when compared with FOLFIRI plus bev. Achieving rapid and deep tumor shrinkage consistently delays tumor progression and prolongs survival in patients treated with first-line chemotherapy plus bev. ETS is a promising and valuable end point for clinical trials' design deserving further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
135
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 9 publications
23
135
0
3
Order By: Relevance
“…These results are slightly improved compared with those of previous studies (9)(10)(11)13,22). Although there is a lack of evidence to determine what molecular mechanisms underlie the effects of rechallenge treatments, a recent clinical result suggests a rationale for this treatment approach (19,23). In the updated results of the Triplet Plus Bevacizumab study, 5-FU, oxaliplatin and irinotecan [FOLFOXIRI] with bevacizumab as a first-line treatment revealed promising efficacy compared with FOLFIRI with bevacizumab (23).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These results are slightly improved compared with those of previous studies (9)(10)(11)13,22). Although there is a lack of evidence to determine what molecular mechanisms underlie the effects of rechallenge treatments, a recent clinical result suggests a rationale for this treatment approach (19,23). In the updated results of the Triplet Plus Bevacizumab study, 5-FU, oxaliplatin and irinotecan [FOLFOXIRI] with bevacizumab as a first-line treatment revealed promising efficacy compared with FOLFIRI with bevacizumab (23).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, early tumor shrinkage (ETS) and depth of response (DoR) have been developed to overcome these problems (16). ETS and DoR have been associated with prolonged PFS, post-progression survival (PPS) and OS (18,19). ETS and DoR were initially developed to predict the efficacy of targeted agents (19), but their roles in conventional chemotherapy have not yet been fully evaluated (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-tumor shrinkage was proposed as a surrogate endpoint for predicting long-term outcome of patients on cetuximab-based systemic chemotherapy [13,14]. Yet the time to first tumor assessment, the method and the cut-off of relative changes in tumor size remain unsettled.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses of randomized clinical trials have suggested a robust association between early tumor shrinkage by 20% or more and OS, independently of treatment arm [13,14]. In contrast large increases in objective "best" response rates modestly translated into OS benefits for first line chemotherapy in patients with mCRC [15,16].…”
Section: Introductionmentioning
confidence: 99%